Research as learning : the realities of action research in a New Zealand individualised learning programme : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University - Poskitt, Jennifer Mary (Massey University, 1994)
The thesis portrays an action research study of an individualised learning programme in a rural New Zealand secondary school. The study considers the nature of action research, individualised and cooperative learning programmes, and the role of innovation and reflection in a school undergoing change. "Achieve", the title of the programme, predominantly encompasses individualised learning although elements of cooperative learning are also included. The fundamental basis of the programme is developing student responsibility for their own learning. The gap between the theoretical and the practical domains of the programme is exposed with students requiring considerable guidance in the transition from teacher-directed to self-directed learners. Various issues arise in the concepts of learning alone and together, the provision of choices and control, and the role of reflection and innovation in schools undergoing change. Inconsistent practices in developing students as independent learners are only made explicit through considerable observation, reflection and critical discourse. Action research is the means through which teachers improve their understandings, situation and practices. However, at the outset, few teachers at this school were ready for action research. Reflective skills are activated and extended through a series of staff discussions, centring around observational and interview data. Teachers gradually become aware of inconsistent understandings and practices. With the involvement of an outside researcher their reflective capacities are developed, research comes to be valued and the quest for data stimulates the development of teachers' own research skills, and changes in the school culture. A three part developmental sequence is proposed for the involvement of outside researchers. It entails a progression from practical to theoretical phases. Various principles and procedures of action research are questioned, among which are: that teachers are ready to and are sufficiently skilled to conduct action research projects, that all teachers are reflective on their practice, and that school cultures are conducive to action research. A tentative theory of readiness is proposed for schools not formerly exposed to action research. The three phases incorporate involvement in a second-order action research study. This enables participants to discern the value and relevance of research, to stimulate interest in and development of reflective research skills, and to develop a questioning inquiry for greater involvement in the research. Thus, a second-order study can be transformed into a first-order action research study, enabling the development of teachers-as-researchers.
Keywords: Computer managed instruction; Educational technology; Individualised instruction; Self-culture